2000
DOI: 10.1007/s001340051152
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II formation and endothelin clearance in ARDS patients in supine and prone positions

Abstract: Acute changes of oxygenation in ARDS patients by positioning do not induce any short-term effects on pulmonary ET-1 net clearance or Ang II net formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…Downregulation of ACE2 may result in the elevated plasma level of Ang II, which is a major substrate of ACE2. Additionally, Ang II is claimed considerably increased in ARDS patients [40]. Consistent with this report, the plasma levels of Ang II were also markedly upregulated in severe pneumonia patients (Figure 3h).…”
Section: Elevated Plasma Levels Of Mir-200c-3p In Severe Pneumonia Pasupporting
confidence: 89%
“…Downregulation of ACE2 may result in the elevated plasma level of Ang II, which is a major substrate of ACE2. Additionally, Ang II is claimed considerably increased in ARDS patients [40]. Consistent with this report, the plasma levels of Ang II were also markedly upregulated in severe pneumonia patients (Figure 3h).…”
Section: Elevated Plasma Levels Of Mir-200c-3p In Severe Pneumonia Pasupporting
confidence: 89%
“…The majority of the studies investigated patients with a predominance (w80% of the studies) of primary ARDS [22, 27, 39-41, 43, 57] while a minority investigated patients with a predominance of secondary ARDS (11%) [24,56,62,63]. Approximately 40% investigated a group of patients with equally distributed primary and secondary ARDS (between 20-80%) [4,5,18,23,26,28,42,50,60,61]. One-third of the studies (33%) did not describe the population studied [25, 51-55, 58, 59].…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Except for two studies performed in pressurecontrolled ventilation [56,60], all were performed in volume-controlled ventilation. The majority of the studies (63%) did not describe the support used for pronation [26,27,39,40,42,43,[51][52][53][54][55][57][58][59][60][61].…”
Section: An Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have suggested a role for the renin-angiotensin system (RAS) in ARDS and VILI [12,[16][17][18]. While the RAS is well known to have a primary role in the control of salt retention and blood pressure, its role in inflammation and injury suggest that is may be a novel therapeutic option for the treatment of ARDS and VILI.…”
Section: Introductionmentioning
confidence: 99%